STRATEGI PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH OLEH PEMERINTAH DESA BUDIDAYA KECAMATAN SIDOMULYO KABUPATEN LAMPUNG SELATAN - Zeizou Indra Pratama; Ardansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Empowering MSMEs in rural areas requires the active role of the village government as the foremost stakeholder in promoting community welfare. The village government does not only function as a facilitator, but also as the main driving force in creating a conducive business climate for MSME actors. The problems encountered include limited access of MSME actors to business capital and financing, low public understanding of business management and digital marketing, as well as limited supporting facilities such as production and distribution infrastructure. The strategy for empowering MSMEs by the Government of Budidaya Village, Sidomulyo District, South Lampung Regency, has been implemented through various programs and activities that focus on increasing the capacity of business actors, providing capital support, and offering business assistance. The village government plays a role as a facilitator and driver in encouraging the development of MSMEs.